2021
DOI: 10.1088/1742-6596/1842/1/012083
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Teacher’s Competencies Profile According to The SAMR Model Framework

Abstract: The purpose of this research was to take inventory of teachers’ experiences and practices in online learning services during Covid-19 were aligned with the SAMR model (substitution, augmentation, modification, and redefinition) as a framework for the formulation of 21st Century Teacher competencies. Formulation of 21st-century teacher competency profiles is specifically developed based on competency standards for Indonesian Teachers, online learning practice experiences during Covid-19, and synergized with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…53(2) 88-93 DOI: 10.24425/ppb.2022 symptoms of burnout in different professional groups (Bochelyuk et al, 2007;Bochelyuk, 2010;Bochelyuk et al, 2016a;Bochelyuk et al, 2016b). Preliminary analysis of the category of professional personality crises from a scientific perspective showed that the construct "professional self-determination" positions the individual not only as a subject of labour, but also as a subject of being in various conditions of life (Hu, 2021;Priyadi et al, 2021;Cobos & González, 2021;Márquez-Álvarez et al, 2021).…”
Section: Original Papersmentioning
confidence: 99%

Polish Psychological Bulletin

Bocheliuk,
Spytska,
Shaposhnykova
et al. 2022
“…53(2) 88-93 DOI: 10.24425/ppb.2022 symptoms of burnout in different professional groups (Bochelyuk et al, 2007;Bochelyuk, 2010;Bochelyuk et al, 2016a;Bochelyuk et al, 2016b). Preliminary analysis of the category of professional personality crises from a scientific perspective showed that the construct "professional self-determination" positions the individual not only as a subject of labour, but also as a subject of being in various conditions of life (Hu, 2021;Priyadi et al, 2021;Cobos & González, 2021;Márquez-Álvarez et al, 2021).…”
Section: Original Papersmentioning
confidence: 99%

Polish Psychological Bulletin

Bocheliuk,
Spytska,
Shaposhnykova
et al. 2022
“…In senior high school, English subject is categorized for a beginner class which is settled to pick up the language in communication delivery, that encourages the students to deliver their comments for the classroom material. The teachers are encouraged to build and connect their students with picking certain vocabulary that connected the classroom discussion (Marlisa Aini et al, 2020;Priyadi et al, 2021;Yusuf et al, 2017). Concerning the idea, by pitching dialogues one to another between teacher and students it is no justification of right or wrong answer, however, why the idea is correct or wrong, why the students confirm the correct or wrong.…”
Section: Introductionmentioning
confidence: 99%